Lactate Threshold Training Program on Patients with Multiple Sclerosis: A Multidisciplinary Approach - Amato, Alessandra; Ragonese, Paolo; Ingoglia, Sonia; Schiera, Gabriella; Schirò, Giuseppe; Di Liegro, Carlo Maria; Salemi, Giuseppe; Di Liegro, Italia; Proia, Patrizia (Nutrients, 2021)
Physical activity could play a key role in improving the quality of life, particularly in patients with nervous system diseases such as multiple sclerosis (MS). Through lactacid anaerobic training, this study aims to investigate the effects at a bio-psycho-physical level to counteract the chronic fatigue associated with the pathology, and to improve mental health at a psychological and neurotrophic level. Eight subjects (age: 34.88 ± 4.45 years) affected by multiple sclerosis were involved. A lactate threshold training program was administered biweekly for 12 weeks at the beginning of the study (T0), at the end of the study (T1) and at 9 months after the end of the study (T2), with physical, psychological and hematochemicals parameters, and dietary habits being tested. The results obtained confirmed that lactacid exercise can influence brain-derived neurotrophic factor (BDNF) levels as well as dehydroepiandrosterone sulfate (DHEAS) levels. In addition, levels of baseline lactate, which could be best used as an energy substrate, showed a decrease after the protocol training. Self-efficacy regarding worries and concerns management significantly increased from T0 to T1. The eating attitudes test (EAT-26) did not highlight any eating disease in the patients with a normal diet enrolled in our study. Physical exercise also greatly influenced the patients psychologically and emotionally, increasing their self-esteem. Lactate threshold training, together with dietary habits, appears to exert synergic positive effects on inflammation, neural plasticity and neuroprotection, producing preventive effects on MS symptoms and progression.